Influence of cell distribution and diabetes status on the association between mitochondrial DNA copy number and aging phenotypes in the InCHIANTI study. Issue 1 (19th October 2017) - Moore, Ann Zenobia; Ding, Jun; Tuke, Marcus A.; Wood, Andrew R.; Bandinelli, Stefania; Frayling, Timothy M.; Ferrucci, Luigi
Summary: Mitochondrial DNA copy number (mtDNA‐CN) estimated in whole blood is a novel marker of mitochondrial mass and function that can be used in large population‐based studies. Analyses that attempt to relate mtDNA‐CN to specific aging phenotypes may be confounded by differences in the distribution of blood cell types across samples. Also, low or high mtDNA‐CN may have a different meaning given the presence of diseases associated with mitochondrial damage. We evaluated the impact of blood cell type distribution and diabetes status on the association between mtDNA‐CN and aging phenotypes, namely chronologic age, interleukin‐6, hemoglobin, and all‐cause mortality, among 672 participants of the InCHIANTI study. After accounting for white blood cell count, platelet count, and white blood cell proportions in multivariate models, associations of mtDNA‐CN with age and interleukin‐6 were no longer statistically significant. Evaluation of a statistical interaction by diabetes status suggested heterogeneity of effects in the analysis of mortality ( P  < 0.01). The magnitude and direction of associations between mtDNA‐CN estimated from blood samples and aging phenotypes are influenced by the sample cell type distribution and disease status. Therefore, accounting for these factors may aid understanding of the relevance of mitochondrial DNA copy number to health and aging.